HUBUNGAN BIMBINGAN BELAJAR SWASTA DENGAN HASIL BELAJAR BIOLOGI - Ristanti, Atika; Sukaesih, Sri; Indriyanti, Dyah Rini (Journal of Biology Education, 2013)
This study aims to describe the correlation tutoring activities and achievement motivation with the results of biological studies. The population in this study were students of class XII SMA Negeri 1 Pemalang. Samples were determined using purposive sample, the class XII science student XII IPA 1 to 5, total 195 students. This type of research is a correlational study. The research data includes data tutoring activities and motivation derived from the scale of student motivation, data motivate students attend private tutoring obtained from interviews and the results of learning from the teacher. Data were analyzed by descriptive quantitative SPSS 16. The study results who that student who attendtutorial private institutions were 60.5% and students who only attend school tutoring were 39.5%. There was a correlation between the activities of tutoring and student learning outcomes (r = 0.148). There was a correlation between learning motivation and learning outcomes of students (r = 0.249). Tutoring activities and motivation indicate a correlation to student learning outcomes (r = 0.284). The process of learning from school guidance sufficient to improve student learning outcomes.Â Penelitian ini bertujuan untuk mendeskripsikan hubungan kegiatan bimbingan belajar swasta dan motivasi belajar dengan hasil belajar biologi.Populasi dalam penelitian ini adalah siswa kelas XII SMA Negeri 1 Pemalang. Sampel ditentukan menggunakan teknik purposive sample, yaitu siswa kelas XII IPA 1 - XII IPA 5 yang berjumlah 195 siswa. Penelitian ini merupakan penelitian korelasional. Data penelitian meliputi data kegiatan bimbingan belajar dan motivasi belajar yang diperoleh dari skala motivasi belajar siswa, data motivasi siswa mengikuti bimbingan belajar swasta diperoleh dari hasil wawancara serta hasil belajar dari guru. Data dianalisis secara deskriptif kuantitatif dengan SPSS 16.Hasil penelitian yang diperoleh yaitu siswa yang mengikuti lembaga bimbingan swasta sebesar 60.5% dan siswa yang hanya mengikuti bimbingan belajar di sekolah sebesar 39.5%. Ada hubungan antara kegiatan bimbingan belajar swasta dan hasil belajar siswa (r=0.148). Terdapat hubungan antara motivasi belajar dan hasil belajar siswa (r=0.249). Kegiatan bimbingan belajar swasta dan motivasi belajar menunjukkan adanya hubungan terhadap hasil belajar siswa (r=0.284). Proses bimbingan belajar dari sekolah cukup untuk meningkatkan kemampuan hasil belajar siswa.